Evaluation of different substrates to support the growth of Typha latifolia in constructed wetlands treating tannery wastewater over long-term operation - Calheiros, Cristina S. C. (2010)
The aim of this study was to investigate the performance of horizontal subsurface flow constructed wetlands planted with Typha latifolia treating tannery wastewater under long-term operation. Two expanded clay aggregates (Filtralite® MR3–8-FMR and Filtralite® NR3–8-FNR) and a fine gravel-FG were used as substrate for the constructed wetland units plus one unit with FMR was left as an unvegetated control. The systems were subject to three hydraulic loadings, 18,8 and 6cm d⁻¹, and to periods of interruption in the feed. The relationship between the substrate, plant development and removal efficiency, especially of organic matter, was investigated. Organic loadings up to 1800 kg BOD5 ha⁻¹ d⁻¹ and 3849 kg COD ha⁻¹ d⁻¹ were applied leading to mass removals of up to 652 kg BOD₅ ha⁻¹ d⁻¹ and 1869 kg COD ha⁻¹ d⁻¹, respectively. The three different substrates were adequate for the establishment of T. latifolia, although the clay aggregates allowed for higher plant propagation levels. The units with FNR and FMR achieved significantly higher COD and BOD₅ removal when compared to the FG and to the unplanted units. The systems proved to be tolerant to high organic loadings and to interruptions in feed suggesting this technology as a viable option for the biological treatment of tannery wastewater.